Análisis de las noticias publicadas del medio digital “La Voz” Isla de Bejucal - Triana Díaz, Kerly Yomira (2023)
The case study is based on the analysis of the content of the digital multimedia “La Voz” and its impact on society or part of it, despite the fact that the origin of the digital medium is located in the Isla de Bejucal parish, Canton. Slime; Being an online platform that is transmitted over the Internet, it can also be seen in other countries. In short, the editors of this agency are dedicated to informative coverage of Ecuadorian events, as well as commercial promotions such as birthdays, promotions of products and services, etc. The interview technique was used to obtain direct information from the owner of the digital medium. The analytical method met the objectives of the study. The target group was two master's students in communication and people familiar with "La Voz". Their followers, opinions and comments also became a form of observation, so the relationship was significant on their Facebook.